Neoliberal urbanism, public space, and the greening of the growth machine: New York City's High Line park. (August 2017) - Lang, Steven; Rothenberg, Julia
In post-industrial cities throughout the world abandoned railroads, demolished freeways, disused canals, and other derelict industrial ruins are being transformed into ecologically inspired and aesthetically designed leisure, consumption, and tourist spaces based upon the principles of Landscape Urbanism and ideas about sustainable park design. New York City's High Line is one example of this growing trend. Sustainable parks like the High Line claim to provide economic, ecological, and equity benefits associated with the 3 Es of sustainability. Our research on the development of New York City's High Line suggests that while the High Line meets the economic piece of the sustainability triad with its promise of generating growth, its success in terms of the ecological dimension of sustainability is unclear. More troubling is the High Line's neglect of the social equity component of the discourse of sustainability. Our work brings together several key arguments in the critical literature on urban sustainability to examine how structural constraints associated with creating post-industrial ecological spaces in a climate of neoliberal urbanization play out in the paradigmatic case of the High Line.